THE EFFECT OF WORK SCHEDULING ON JOB SATISFACTION IN DR RM DJOELHAM BINJAI - Hendra Frizky Novando; Yeni Absah; Rulianda Wibowo (CV. Radja Publika, 2023)
Scheduling determines when activities are started, postponed, and completed to adjust resource use to predetermined needs. Labor scheduling helps every company improve employee performance. Job scheduling affects job satisfaction—how people feel about different aspects of their work. This quantitative study examines how work scheduling affects job satisfaction. This study includes 420 civil servants at the Regional General Hospital DR RM Djoelham (PNS). Non-probability sampling yielded 100 research samples. Simple linear regression and questionnaire data collection. The study found that scheduling affects job satisfaction positively and significantly. T-count X (12.721) > t-table (1.98) and p-value (0.000) <0.05 indicate it. 46 people (46.0%) work at DR RM Djoelham Binjai Hospital, which is good. The majority of DR RM Djoelham Binjai Hospital employees (49.0%) are satisfied with their jobs. The DR RM Djoelham Binjai Hospital's work scheduling steps should be more systematic so that all employees can follow them. Hospital leaders should focus more on job satisfaction factors to improve job satisfaction in the future.